High-flame-retardant high-viscosity glass fiber grid double-sided fixing adhesive tape
By doping nanoscale additives and nanofiber membranes into the double-sided fixed tape of glass fiber mesh, and combining ultra-temperature-resistant heat-insulating fiber cotton and dynamic chemical bond recombination mechanism, the problem of insufficient flame retardancy, viscosity and mechanical properties of existing tapes is solved, and high flame retardant, high viscosity and high mechanical properties of tapes are achieved, which are suitable for a variety of complex application scenarios.
Patent Information
- Application Number
- CN202510426366.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2025-05-09
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing tapes are difficult to take into account both flame retardancy, high viscosity and mechanical properties, and cannot meet the strict requirements in the fields of electronic equipment manufacturing, building fire protection, etc.
The double-sided fixing tape of high flame retardant and high viscosity glass fiber mesh is used to dopant nanoscale titanium dioxide and silica composite additives in the glass fiber mesh and cover the nano-scale polymer fiber membrane on the surface, combining ultra-temperature-resistant heat-insulating fiber cotton and dynamic chemical bond recombination mechanism to improve the comprehensive performance of the tape.
It realizes the high flame retardant, strong viscosity and high mechanical properties of the tape, and can maintain long-term stability in high temperature, high humidity and low temperature drying environments, and is suitable for complex working conditions and extreme environments.
Smart Images

Figure CN119955426A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of double-sided fixing tapes, in particular to a high-flame-retardant and high-viscosity glass fiber mesh double-sided fixing tape. Background Art
[0002] In today's industry and daily life, tapes are widely used. However, in areas such as electronic equipment manufacturing, building fire protection, and automobile manufacturing, which have strict requirements on tape performance, existing ordinary tapes have exposed many shortcomings. In electronic equipment manufacturing, electronic components may generate high temperatures during operation. Once a fire occurs, the tapes used in the surrounding area need to have flame retardant properties to prevent the spread of the fire and cause serious damage to the entire equipment; at the same time, the tapes must have sufficient viscosity to stabilize the electronic components and ensure that they will not shift due to vibration and other factors during the operation of the equipment. In the field of building fire protection, tapes used for connecting and sealing building materials must not only meet certain strength requirements and be able to withstand small displacements and external forces of the building structure, but also be able to effectively prevent the spread of flames and heat when a fire occurs, so as to buy time for personnel evacuation and fire rescue.
[0003] Most tapes on the market today are unable to simultaneously take into account flame retardancy, high viscosity and other key properties. They either have poor flame retardancy and cannot meet specific flame retardancy standards; or they are not strong enough to easily debond in actual use; or they have poor mechanical properties, such as insufficient shear strength and fracture strength, and cannot meet the application scenarios of withstanding large external forces. Therefore, the development of a glass fiber mesh double-sided fixing tape that combines high flame retardancy, high viscosity and other excellent properties has important practical significance and market demand.
[0004] In view of this, a highly flame-retardant and high-viscosity glass fiber mesh double-sided fixing tape is provided to overcome the above problems. Summary of the invention
[0005] The object of the present invention is to provide a highly flame-retardant and high-viscosity glass fiber mesh double-sided fixing tape to solve the problems raised in the above background technology.
[0006] In order to solve the above technical problems, the present invention provides a highly flame-retardant and high-viscosity glass fiber mesh double-sided fixing tape, comprising: First acrylic glue, first glass fiber mesh, super heat-resistant heat-insulating fiber cotton, second glass fiber mesh, second acrylic glue, release paper; The first glass fiber mesh and the second glass fiber mesh are uniformly doped with nano-scale titanium dioxide and silicon dioxide composite additives. Nano-scale titanium dioxide has good photocatalytic activity and chemical stability, and silicon dioxide has high hardness, high insulation and other characteristics. The combination of the two can effectively improve the comprehensive performance of the glass fiber mesh; and a layer of nano-scale polymer fiber film is evenly covered on the surface of the glass fiber, which can enhance the wear resistance and corrosion resistance of the glass fiber; and the surface of the glass fiber has a microscopic rough structure, which increases the contact area with the adhesive layer and is conducive to improving the bonding force; the internal fibers are in a bionic honeycomb structure and are closely arranged in hexagons. This structure ensures that the glass fiber mesh has a light weight while ensuring high strength, further improving the mechanical properties of the tape; The super heat-resistant heat-insulating fiber cotton uses a new type of ceramic-based composite fiber as the main raw material. The new type of ceramic-based composite fiber has the characteristics of high temperature resistance, high strength, low density, etc., which provides good basic performance for the fiber cotton; nano-scale aerogel particles are evenly dispersed in the fiber, and the aerogel has an extremely low thermal conductivity, which can greatly enhance the heat insulation performance of the fiber cotton; at the same time, rare earth compounds with infrared blocking function are added to effectively block the propagation of infrared rays and further enhance the heat insulation effect; the fibers in the microstructure form a three-dimensional porous network structure, which increases the air retention space and reduces the heat conduction efficiency, and a nano protective film is provided on the fiber surface to prevent the fiber from being eroded by the external environment and ensure the stability of the fiber cotton performance; The first glass fiber grid and the second glass fiber grid are respectively located at the top and bottom of the super heat-resistant and heat-insulating fiber cotton to form a stable support frame; the first acrylic glue and the second acrylic glue are respectively located at the top and bottom of the first glass fiber grid and the second glass fiber grid to give the tape adhesive properties; the release paper is located at the bottom of the second acrylic glue to protect the glue surface.
[0007] Furthermore, the glass fiber mesh gluing process includes raw material inspection, primer application, glue layer coating, glue surface inspection, and winding.
[0008] Furthermore, the preparation process of the super heat-resistant heat-insulating fiber cotton includes raw material inspection, needling, combing, shaping, testing, and winding.
[0009] Furthermore, the overall production process includes unwinding, laminating, adhesive surface detection, winding, slitting, finished product inspection, packaging, labeling, warehousing, and shipping.
[0010] Furthermore, a dynamic chemical bond recombination mechanism based on biomimetics is introduced for microstructure self-repair. A polymer network with reversible chemical bonds is constructed through the synthesis of special monomers and introduced into the tape microstructure.
[0011] Furthermore, the synthesis of special monomers is based on the study of dynamic chemical bonds and supramolecular interactions, and monomers containing borate groups or disulfide bonds that can form dynamic covalent bonds and groups with supramolecular interaction capabilities are synthesized, including but not limited to ureidopyrimidone.
[0012] Furthermore, during the polymer network construction process, a crosslinking agent such as pentaerythritol triacrylate is introduced to adjust the crosslinking density, and an initiator is added, including but not limited to azobisisobutyronitrile to initiate the monomer polymerization reaction.
[0013] Furthermore, micro-defect structures are constructed and material distribution is adjusted to concentrate stress in the microstructure, and stress-sensitive additives are introduced and molecular-guided structures are designed to promote dynamic chemical bond breaking and recombination.
[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. High viscosity guarantee: First, acrylic adhesive gives the tape strong viscosity due to its chemical properties, which can stabilize electronic components and ensure that they will not shift due to vibration during the operation of electronic equipment; in the construction field, it can ensure that materials are firmly connected, solving the problem of insufficient viscosity of existing tapes.
[0015] Improved strength: The first and second glass fiber grids form a stable supporting structure. Their high strength and rigidity significantly improve the shear and fracture strength of the tape, meeting the building structure's requirements for bearing displacement and external forces, and solving the problem of poor mechanical properties of existing tapes.
[0016] Excellent thermal insulation and flame retardancy: The ultra-heat-resistant thermal insulation fiber cotton in the middle layer, with its special material and low thermal conductivity structure, can prevent components from running at high temperatures in electronic equipment manufacturing, and can prevent the spread of flames and heat during building fire protection, solving the problem of poor flame retardancy of existing tapes.
[0017] Adhesive surface protection: The release paper at the bottom of the second acrylic adhesive protects the adhesive surface during storage and transportation, prevents contamination and premature adhesion, and maintains good adhesion and performance when the tape is used.
[0018] The first glass fiber grid and the second glass fiber grid are uniformly doped with nano-scale titanium dioxide and silicon dioxide composite additives, the surface is covered with nano-scale polymer fiber membrane, and the internal fibers are closely arranged in a bionic honeycomb structure. The shear strength of the tape is increased by 30%, and the breaking strength is increased by 32%, which can better meet the needs of building structures to withstand larger displacements and external forces under the influence of earthquakes, wind, etc.
[0019] The super heat-resistant thermal insulation fiber cotton uses a new type of ceramic-based composite fiber as the main raw material, evenly disperses nano-aerogel particles and adds rare earth compounds with infrared blocking function. Its thermal conductivity is 40% lower than that of traditional fiber cotton. In the manufacture of electronic equipment, it can effectively block the high temperature generated by the operation of components. In building fire prevention, it can more efficiently prevent the spread of flames and heat, buying more time for personnel evacuation and fire rescue.
[0020] The microscopic rough structure of the glass fiber surface increases the bonding force with the adhesive layer. The three-dimensional porous network structure of the ultra-heat-resistant and heat-insulating fiber cotton and the nano-protective film on the fiber surface enable it to better resist the influence of the external environment. Through long-term use tests simulating different environments, according to GB / T2423.3-2016 "Environmental Testing Part 2: Test Method Test Cab: Constant Humidity Test", GB / T2423.1-2008 "Environmental Testing Part 2: Test Method Test A: Low Temperature" and other standards, in high temperature and high humidity (temperature 85℃, relative humidity 85%), low temperature and dry (temperature -20℃, relative humidity 30%) and other environments, after 1000 hours of testing, the tape using this structure and material did not show obvious degumming and performance degradation, while the ordinary tape showed different degrees of degumming and performance degradation, with the degumming area accounting for 10%-20% and the performance degradation degree reaching 15%-30%, which fully proved the long-term stability of the performance of the tape.
[0021] In the production of tapes, each process closely controls quality and improves production efficiency. The glass fiber mesh gluing process ensures the quality and performance of the glass fiber mesh through strict raw material inspection, brushing of primer, coating of flame-retardant glue layer, glue surface inspection and winding, laying the foundation for the flame retardant and adhesive properties of the tape. The preparation process of ultra-heat-resistant thermal insulation fiber cotton improves the thermal insulation and flame retardant properties of the fiber cotton through raw material inspection, needle punching, adding flame-retardant thermal insulation powder, combing, shaping, testing and winding. The overall production process, from precise control of unwinding tension to multi-layer hot pressing composite, glue surface inspection, winding, slitting, finished product inspection, packaging, labeling, warehousing and shipping, ensures the stability and consistency of product quality, improves production efficiency, and meets diversified production and market needs.
[0022] This tape has excellent performance, reaching the flame retardant VO level, with strong adhesion, high shear strength and breaking strength, and low thermal conductivity, which makes it excellent in thermal insulation and flame retardant properties. In addition to the pasting function, it also has a compressive support function, is compressible, and can maintain structural integrity under complex stress environments. It can be rolled up without stratification, which is convenient for storage and transportation. At the same time, it can be used with automated application to improve production efficiency. In terms of production technology, the glass fiber mesh is coated with flame retardant glue to enhance the tensile properties, the fiber needle punching adds flame retardants and thermal insulation powder to optimize the thermal insulation and flame retardant properties, the multi-layer hot pressing composite makes the structure tighter, and the CCD detection of the adhesive surface appearance ensures product quality.
[0023] By introducing a dynamic chemical bond reorganization mechanism based on biomimetic to achieve microstructure self-repair, the performance of the tape has been significantly improved. The performance stability has been effectively enhanced, and the microscopic damage caused by external forces can be repaired in time, and the high flame retardancy, high viscosity, and high strength of the tape can be continuously maintained, ensuring the stability of components and preventing fire hazards in the manufacture of electronic equipment. At the same time, the service life is greatly extended, and the structure and performance can be kept stable for a long time in the field of building fire protection, reducing the replacement frequency and cost.
[0024] This tape can adapt to extremely complex working conditions. When faced with strong mechanical stress, high and low temperature cycles, radiation and other combined effects in the aerospace field, it can still maintain good performance and ensure the normal operation and safety of components. It also reduces maintenance costs and risks. In applications such as automobile manufacturing, it reduces the workload of manual maintenance and reduces the potential risks caused by tape failure. This self-repairing tape has formed a differentiated competitive advantage with new technologies, opened up a new direction for the development of the tape industry, attracted more customers who have demand for high-performance, long-life tapes, and expanded the application field and market space. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram of the cross-sectional structure of a high flame retardant and high viscosity glass fiber mesh double-sided fixing tape of the present invention; Figure 2 The schematic diagram of the high flame retardant and high viscosity glass fiber mesh double-sided fixing tape of the present invention is shown.
[0026] In the figure: 1. first acrylic glue; 2. first glass fiber mesh; 3. super heat-resistant heat-insulating fiber cotton; 4. second glass fiber mesh; 5. second acrylic glue; 6. release paper. DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] See also Figure 1-Figure 2 , the present invention provides a technical solution: See also Figure 1-Figure 2 As shown, a first embodiment of a highly flame-retardant and highly viscous glass fiber mesh double-sided fixing tape: 1. Tape structure A highly flame-retardant and high-viscosity glass fiber mesh double-sided fixing tape comprises a first acrylic adhesive 1, a first glass fiber mesh 2, super-heat-resistant and heat-insulating fiber cotton 3, a second glass fiber mesh 4, a second acrylic adhesive 5, and a release paper 6.
[0029] The first glass fiber mesh 2 and the second glass fiber mesh 4 are respectively located on the top and bottom of the super heat-resistant heat-insulating fiber wool 3, and this structure builds a stable support frame for the tape. The glass fiber mesh can effectively disperse external forces with high strength and rigidity to prevent the tape from being deformed or damaged when subjected to force.
[0030] The first acrylic adhesive 1 and the second acrylic adhesive 5 are respectively located at the top and bottom of the first glass fiber mesh 2 and the second glass fiber mesh 4. The good viscosity of the acrylic adhesive gives the tape excellent adhesion performance, so that it can be firmly adhered to the surfaces of various objects.
[0031] The release paper 6 is located at the bottom of the second acrylic adhesive 5, and its function is to protect the adhesive surface during storage and transportation, prevent the adhesive surface from being contaminated or prematurely sticking, and ensure that the viscosity of the tape is not affected during use.
[0032] Fiberglass mesh preparation In the preparation process of glass fiber mesh, nano-scale titanium dioxide and silicon dioxide composite additives are accurately weighed by metering equipment, accounting for 3% of the mass of glass fiber raw materials, and are evenly mixed into the glass fiber raw material system using a high-speed stirring and dispersing device. According to the "Technical Specifications for the Application of Composite Material Additives" and a large amount of experimental data, when the mass proportion of the composite additive in glass fiber is in the range of 2%-5%, it can effectively improve its tensile strength, bending modulus and other mechanical properties and chemical stability while maintaining the basic physical and chemical properties of glass fiber. Among them, the 3% ratio has been verified by mechanical properties tests under multiple batches and multiple conditions (according to GB / T3354-2014 "Test Method for Tensile Properties of Oriented Fiber Reinforced Polymer Matrix Composite Materials", GB / T9341-2008 "Determination of Bending Properties of Plastics" and other standards). The tensile strength of the glass fiber mesh is increased by about 20%, the bending modulus is increased by about 15%, and the stability improvement effect is significant.
[0033] A specially designed melt spinning process is used to precisely control parameters such as spinning temperature, pressure, and nozzle aperture (temperature is controlled at 1200-1300℃, pressure is 0.5-0.8MPa, and nozzle aperture is 0.05-0.1mm) to evenly disperse the additives in the internal microstructure of the glass fiber. After the glass fiber is formed, chemical vapor deposition (CVD) equipment is used to use organic compounds such as silanes and titanates as precursors to uniformly deposit nano-scale polymer fiber membranes on the surface of the glass fiber under high temperature (800-1000℃) and low pressure (10-100Pa). The membrane thickness is precisely controlled to be 50nm. Referring to the "Material Surface Coating Technology Manual" and related research results, when the membrane thickness is in the range of 30-80nm, it can effectively enhance the surface hardness, wear resistance, and chemical corrosion resistance of the glass fiber. According to the Vickers hardness test (performed in accordance with GB / T4340.1-2009 "Vickers hardness test for metallic materials - Part 1: Test method"), when the film thickness is 50nm, the surface hardness of the glass fiber increases by about 30%. After immersion in 5% hydrochloric acid solution and 10% sodium hydroxide solution for 24 hours, the mass loss rate is less than 5%, which can effectively improve the comprehensive performance of the glass fiber.
[0034] The glass fiber is initially shaped during the drawing process through a customized mold with a hexagonal microporous structure, and then stretched using a biaxial stretching device at a certain temperature (500-600°C) and stretching rate (0.5-1.0mm / s) to form a bionic honeycomb structure with dense hexagonal arrangement. This structure has been observed by scanning electron microscopy (SEM) and finite element mechanical analysis, and while ensuring the lightweight characteristics of the glass fiber, its compressive strength is increased by about 25% compared to conventional structures, effectively enhancing the mechanical properties of the glass fiber grid.
[0035] Preparation of super heat-resistant heat-insulating fiber cotton Using the new ceramic-based composite fiber as the starting material, in the process of opening and combing, with the help of a quantitative feeding device, nano-scale aerogel particles are evenly mixed into the fiber system at a ratio of 10% of the fiber raw material mass. According to "Principles and Applications of Thermal Insulation Materials" and related research reports, when the mass proportion of aerogel particles in fiber cotton is in the range of 8%-15%, the thermal conductivity of fiber cotton can be significantly reduced. According to the steady-state heat flow meter method (performed in accordance with GB / T10295-2008 "Thermal flow meter method for the determination of steady-state thermal resistance and related properties of thermal insulation materials"), when the proportion is 10%, the thermal conductivity of fiber cotton is reduced by about 45% compared with when no aerogel particles are added. While effectively improving the thermal insulation performance, the fiber flexibility test (performed in accordance with the internal flexibility test standards of the relevant industry) shows that the effect on the flexibility of fiber cotton is negligible.
[0036] At the same time, rare earth compounds with infrared blocking function (such as yttrium oxide, cerium oxide, etc.) accounting for 5% of the fiber raw material mass are added. According to "Application of Rare Earth Materials in Functional Materials" and related experimental data, at this addition ratio, through Fourier transform infrared spectrometer (FT-IR) test, in the 8-14μm infrared band, the fiber cotton's infrared blocking rate reaches more than 85%, which can effectively block the propagation of infrared rays and further improve the heat insulation effect. X-ray diffraction (XRD) analysis shows that it will not have a negative impact on the crystal structure and overall microstructure of the fiber cotton.
[0037] After the needle punching process, the needle punching depth is controlled to 8-10mm and the needle punching density is controlled to 200-300 needles / cm², so that the fibers are initially interwoven into a three-dimensional network structure. Then, through the hot pressing process, the temperature is 150-180℃ and the pressure is 1-2MPa. The hot pressing is performed to shape the fibers to form a stable three-dimensional porous network structure.
[0038] Finally, the sol-gel method was used, with silica sol as the main raw material, and an appropriate amount of catalyst (such as hydrochloric acid, adjusting the pH value to 2-3) and cross-linking agent (such as tetraethyl orthosilicate) were added to form a nano protective film on the fiber surface, and the thickness of the protective film was precisely controlled to be 30nm. According to the "Principles of Material Surface Protection Technology" and related research, when the thickness of the protective film is 20-40nm, it can effectively prevent the fiber from being eroded by the external environment (such as humidity, ultraviolet rays, etc.). After accelerated aging tests (performed in accordance with GB / T16422.2-2014 "Plastic Laboratory Light Source Exposure Test Method Part 2: Xenon Arc Lamp"), after aging for 1000h under simulated natural environment light and humidity conditions, the retention rate of various properties of the fiber cotton was above 90%, ensuring the long-term stability of the fiber cotton performance.
[0039] (II) Process flow Overall process: covers the preparation of glass fiber mesh glue coating and super heat-resistant insulation fiber cotton 3, unwinding (OP70), compounding (OP80), glue surface detection (OP90), winding (OP10), slitting (OP110), finished product inspection (OP120), packaging (OP130), labeling (OP140), warehousing (OP150), shipment (OP160) and other links. This is based on the continuity of industrial production and the need for quality control. Each link is closely linked, and the quality of the previous link directly affects the quality of the subsequent links and the final product. This process design ensures the efficiency of tape production and the stability of product quality. Through step-by-step process operations, each production stage can be strictly controlled, problems can be discovered and solved in a timely manner, the defective rate can be reduced, and production efficiency can be improved. At the same time, it is also convenient for product traceability and management.
[0040] Fiberglass mesh gluing steps: Raw material inspection (OP10): The quality of raw materials used for glass fiber mesh gluing is directly related to the performance of the tape, such as flame retardancy, bonding performance, etc. Only by ensuring the quality of raw materials can the subsequent production of tapes meet the quality standards, ensuring product quality from the source, avoiding product performance defects caused by raw material problems, reducing scrap rates, and lowering production costs.
[0041] Apply primer (OP20): Choose a primer that is compatible with the fiberglass mesh and the subsequent adhesive layer to enhance the adhesion between the adhesive layer and the fiberglass mesh. The surface of the fiberglass mesh is relatively smooth, and directly applying the adhesive layer may result in a loose bond. The primer can form a transition layer between the fiberglass mesh and the adhesive layer, improving the bonding strength between the two, making the adhesive layer and the fiberglass mesh more firmly bonded, improving the overall strength and durability of the tape, and making it less likely for the adhesive layer to fall off during use.
[0042] Coating adhesive layer (OP30): Accurately prepare flame retardant glue according to the formula requirements and evenly apply it through a specific coating process, in order to give the fiberglass mesh good flame retardant properties. Even coating can ensure the consistency of flame retardant properties, avoid the situation of insufficient local flame retardant properties, and give the fiberglass mesh flame retardant properties, so that the tape can be used in scenes with high fire protection requirements, effectively prevent the spread of flames, and provide reliable fire protection for the use environment.
[0043] Adhesive surface inspection (OP40): Use optical microscopes and other equipment to inspect the adhesive surface quality, and timely find out whether there are bubbles, impurities, uneven coating, etc. on the adhesive surface. These problems will affect the adhesive performance and appearance quality of the tape. Ensure that the adhesive surface quality meets the standards, improve the product qualification rate, ensure that the tape can perform its adhesive function normally when used, and also improve the appearance quality of the product.
[0044] Winding (OP50): Wind the qualified fiberglass mesh to facilitate subsequent transportation and use. It is also convenient for operation in subsequent processes, storage and transportation, and provides convenience for subsequent composite processes, improving production continuity.
[0045] Preparation steps of super heat-resistant insulation fiber cotton 3: Raw material inspection (OP10): The raw material quality of super heat-resistant thermal insulation fiber cotton 3 plays a key role in its final thermal insulation and flame retardant properties. Only when the raw material quality is up to standard can fiber cotton with excellent performance be produced, which ensures the quality of super heat-resistant thermal insulation fiber cotton 3 and lays the foundation for the production of tapes with excellent thermal insulation and flame retardant properties.
[0046] Needle punching (OP20): Adding flame retardants and thermal insulation powder in precise proportions during the needling process can improve the flame retardancy and thermal insulation properties of fiber cotton. Through needling, these additives can be evenly distributed in the fiber raw materials, forming a close bond with the fibers, improving the flame retardancy and thermal insulation properties of the fiber cotton, so that the tape can effectively block the transfer of heat in a high temperature environment, and better prevent the spread of flames when encountering a fire source.
[0047] Combing (OP30): Using a roller combing machine to comb the needle-punched fiber cotton can make the fiber arrangement more neat and orderly, and remove impurities and short fibers in the fiber. Neatly arranged fibers can improve the uniformity and quality of the fiber cotton, thereby improving its thermal insulation performance, improving the uniformity and quality of the fiber cotton, enhancing its thermal insulation performance, and making the thermal insulation effect of the tape more stable and reliable.
[0048] Forming (OP40): Put the carded fiber cotton into a specific forming device, and set the appropriate forming temperature, time and pressure parameters according to its characteristics and product requirements to ensure the stability of the shape and performance of the fiber cotton. In the subsequent processing and use process, stable shape and performance are important factors to ensure the quality of the tape, ensuring that the fiber cotton will not deform or change in performance during the subsequent processing and use process, thus ensuring the quality stability of the tape.
[0049] Testing (OP50): Use professional equipment such as thermal conductivity testers to conduct comprehensive testing on the finalized super heat-resistant thermal insulation fiber cotton 3, which can accurately evaluate its key indicators such as thermal conductivity and flame retardant properties. Only fiber cotton with test results that fully meet the standards can enter the next stage to ensure the performance of the final product, ensure that the fiber cotton entering the subsequent process is of qualified quality, and ensure that the final produced tape has good thermal insulation and flame retardant properties.
[0050] Winding (OP60): Wind the qualified fiber cotton to facilitate the subsequent unwinding and laminating operations, improve production efficiency, facilitate storage and transportation, and provide convenience for the subsequent tape production process.
[0051] (III) Tape performance Excellent performance indicators: Flame retardant VO level: By adding flame retardants during the preparation of glass fiber mesh glue and super heat-resistant insulation fiber cotton 3, the tape reaches flame retardant VO level. Flame retardants can decompose and produce non-combustible gas when encountering a fire source, isolating oxygen and thus preventing the spread of flames. When encountering a fire source, it can quickly extinguish itself and effectively prevent the spread of flames, providing reliable fire protection for the use environment. It can be widely used in fields with high fire protection requirements such as electronic equipment manufacturing and building fire protection.
[0052] Strong adhesion: The characteristics of the first acrylic adhesive 1 and the second acrylic adhesive 5 give the tape good adhesion. The high molecular polymer in the acrylic adhesive can form a strong intermolecular force with the surface of the object to be adhered, thereby achieving a firm adhesion, and can be firmly adhered to the surface of various objects, and is not prone to debonding, ensuring that the tape can stably fix the object during use.
[0053] High shear strength: The high strength of the fiberglass mesh and the firm combination of the adhesive layer and the fiberglass mesh enable the tape to maintain a good bond when subjected to external forces parallel to the bonding surface. The fiberglass mesh can disperse the shear force, while the adhesive layer provides bonding force. When subjected to external forces parallel to the bonding surface, it can maintain a good bond and is not easily damaged by shearing. It is suitable for application scenarios that need to withstand large external forces, such as joints in building structures.
[0054] High breaking strength: The high strength of the fiberglass mesh and the close connection between the layers of the tape enable the tape to withstand greater tension. The fiberglass mesh acts as a skeleton, which enhances the overall strength of the tape, allowing it to withstand greater tension and is not easy to break, ensuring the reliability of the tape during use.
[0055] Low thermal conductivity, excellent thermal insulation and flame retardant performance: The special structure and composition of the super heat-resistant thermal insulation fiber cotton 3, as well as the thermal insulation powder added therein, make it have low thermal conductivity. The thermal insulation powder can block the conduction of heat, and the structure of the fiber cotton can form a thermal insulation barrier, which can effectively block the transfer of heat in a high temperature environment and protect the adhered object from the influence of high temperature, making it suitable for applications in a high temperature environment.
[0056] Multifunctional features: Compression support: The rigidity of the glass fiber grid and the support of the super heat-resistant and heat-insulating fiber cotton 3 enable the tape to provide reliable support in some occasions that need to withstand a certain amount of pressure, such as gap filling in building structures. The glass fiber grid can withstand pressure, and the fiber cotton can play a role of buffering and auxiliary support. In occasions such as gap filling in building structures and fixing equipment components, it can provide reliable support and ensure the stability of the structure.
[0057] Compressible: The super heat-resistant and heat-insulating fiber cotton 3 has a certain elasticity and compressibility, and can deform to a certain extent when squeezed by external force. The fiber structure of the fiber cotton can be displaced and deformed under pressure, and can deform to a certain extent when squeezed by external force, absorbing some energy while maintaining its own structural integrity and will not be easily damaged, thereby improving the adaptability of the tape.
[0058] Can be rolled without delamination: Through reasonable production process and quality control, the tape can be rolled without delamination during the production process. The multi-layer hot pressing composite process makes the layers tightly combined without delamination, which is convenient for storage and transportation, ensuring the stability of product quality and facilitating large-scale production and sales.
[0059] Able to cooperate with automatic pasting: The dimensional accuracy and surface quality of the tape, as well as its stickiness and flexibility, make it well matched with the automatic pasting equipment. The consistency and stability of the tape enable the automatic equipment to accurately perform pasting operations, and efficient automatic pasting operations can be achieved in industrial production, greatly improving production efficiency and reducing labor costs.
[0060] 4. Specific production operations Raw material preparation: Raw materials are prepared strictly in accordance with quality standards and specifications to ensure product performance and quality stability. Different raw material quality will have a significant impact on the performance of the tape, ensuring product quality from the source to avoid product quality fluctuations caused by raw material problems.
[0061] Adhesive tape production: Unwinding (OP70): The unwinding tension of the glass fiber mesh and super heat-resistant insulation fiber cotton 3 is precisely controlled by the tension control system to ensure that they maintain a stable operating state during the unwinding process. Unstable unwinding tension may cause the material to stretch, deform or relax, affecting the subsequent composite quality. Ensure that the unwinding process is stable, provide a good material state for the subsequent composite process, and ensure the composite quality.
[0062] Composite (OP80): Multi-layer hot pressing composite equipment is used to strictly control the parameters such as temperature, pressure and time of hot pressing, so as to make the adhesive fully melt, enhance the bonding force between the layers, and ensure that the layers can fit tightly together. Appropriate temperature, pressure and time can make the adhesive diffuse to the interface of each layer of material, forming a strong chemical bond or intermolecular force, making the structure of the tape more compact and the bonding force between the layers stronger, thereby improving the overall performance of the tape, such as strength and stability.
[0063] Adhesive surface inspection (OP90): Using advanced CCD inspection technology, it can quickly and accurately capture the image information of the adhesive surface, analyze the image through image processing software, and detect whether there are bubbles, impurities, uneven coating, scratches and other defects on the adhesive surface. These defects will affect the appearance and performance of the tape, ensuring the stability and consistency of product quality, effectively reducing the defective rate, and improving the market competitiveness of the product.
[0064] Winding (OP10): Control the winding speed and tension to ensure that the tape is wound tightly and smoothly, which is convenient for subsequent slitting and packaging. Loose or uneven winding will affect the slitting accuracy and packaging quality, which will facilitate the subsequent slitting and packaging processes and ensure the product appearance quality and packaging effect.
[0065] Slitting (OP110): According to the product specifications, use slitting equipment to cut large rolls of tape into small rolls of different widths and lengths. Ensuring the sharpness and precision of the slitting tool is to ensure that the edges of the slitting tape are neat and burr-free, and the size meets the design requirements. Untidy edges and tapes that do not meet the size requirements will affect the use and sales of the product. To meet the needs of different customers, improve the applicability of the product, and at the same time ensure the quality and appearance of the product.
[0066] Finished product inspection (OP120): A comprehensive finished product inspection is carried out on each roll of slit tape, including appearance inspection, dimension measurement, performance test, etc., to ensure that the product meets the quality standards. Only products that pass all inspection items are judged as qualified products, which ensures the quality of the factory products and maintains the reputation of the company and the interests of customers.
[0067] Packaging (OP130): According to the characteristics of the product and customer needs, choose appropriate packaging materials and packaging methods, such as plastic film packaging, paper box packaging, etc., to ensure that the tape is well protected during transportation and storage. Different packaging materials and methods have different protective effects on the product, avoiding damage during transportation and storage, and ensuring product quality.
[0068] Label (OP140): Clear and accurate labels are affixed to product packaging. The label content includes information such as product name, specification model, production date, shelf life, manufacturer, product performance indicators, etc., in order to facilitate users to identify and use the product. Accurate information can help users correctly select and use tapes, improve product traceability and user experience, and facilitate users to understand relevant information about the product.
[0069] Warehousing (OP150): Store the packaged and labeled products in the warehouse according to the specified storage conditions, and ensure that the ambient temperature and humidity of the warehouse meet the product requirements, in order to ensure the stability of product quality during storage. An inappropriate storage environment may affect the performance of the tape, ensuring the quality of the product during storage and reducing product quality problems caused by improper storage.
[0070] Shipping (OP160): Before shipping, the products are checked and inspected again to ensure that the quantity, specifications, quality, etc. of the shipped products are consistent with the customer's order. This is to ensure that customers can receive products that meet their requirements, improve customer satisfaction, and maintain good customer relationships. Example
[0071] (I) Necessity of Example 2 In actual applications, even though the adhesive tape of Example 1 already possesses many excellent properties such as high flame retardancy, high viscosity, and high strength, the microstructure of the adhesive tape may still be gradually damaged in a complex use environment, such as when subjected to repeated external friction, stretching, extrusion, etc. Although this microstructural damage may not significantly affect the macroscopic properties of the adhesive tape in the early stage, with the passage of time and the accumulation of damage, the performance of the adhesive tape will gradually decline, such as reduced viscosity and weakened strength, which will ultimately affect its service life and reliability. Traditional repair methods are difficult to achieve effective repair of microstructural damage. Therefore, in order to further improve the performance and service life of the adhesive tape and meet the higher performance requirements of the adhesive tape in various complex application scenarios, it is very necessary to introduce a dynamic chemical bond recombination mechanism based on biomimetic on the basis of Example 1 to realize the self-repair function of the microstructure of the adhesive tape in Example 2.
[0072] 2. Related contents of microstructure self-repair Raw material selection and preparation: Synthesis of special monomers: Based on the study of dynamic chemical bonds and supramolecular interactions, monomers with specific functional groups and spatial structures are designed. For example, monomers containing borate groups or disulfide bonds that can form dynamic covalent bonds are synthesized, and groups with supramolecular interaction capabilities, such as ureidopyrimidone (UPy), are introduced at the same time. These special functional groups and structures enable the monomers to form a polymer network with reversible chemical bonds after polymerization, thereby achieving self-repair of the microstructure. Taking the synthesis of borate monomers as an example, suitable boric acid and olefin compounds containing hydroxyl groups are selected as raw materials. In an anhydrous and oxygen-free reaction environment, toluene is used as a solvent, an appropriate amount of p-toluenesulfonic acid pyridinium salt catalyst is added, and boric acid and olefin compounds are added to the reaction system at a molar ratio of 1:1.2. The reaction is carried out under heating reflux conditions (temperature controlled at 110-120°C) for 12-16 hours. After the reaction is completed, toluene is removed by vacuum distillation, and the product is separated and purified by column chromatography to obtain a pure borate monomer. This synthesis method can ensure the purity of the monomers and the accuracy of the structure, laying the foundation for the subsequent formation of a polymer network with good self-healing properties.
[0073] The synthesized special monomer provides the key raw material for constructing a polymer network with self-healing ability. Its unique structure enables the polymer network to repair its microstructure through the breaking and recombination of dynamic chemical bonds when damaged by external forces, significantly improving the durability and reliability of the tape.
[0074] Preparation of polymer network construction related additives: Introducing crosslinking agents: Selecting acrylic compounds with multifunctional groups, such as pentaerythritol triacrylate (PETA), as crosslinking agents is used to regulate the crosslinking density of the polymer network. According to the required polymer network performance, the amount of crosslinking agent added is generally 3%-8% of the total monomer mass. The addition of crosslinking agents can form crosslinked structures between polymer molecular chains and enhance the mechanical properties and stability of the polymer network.
[0075] By reasonably controlling the amount of cross-linking agent added, the cross-linking density of the polymer network can be optimized, so that the tape not only has good self-healing properties but also has sufficient strength and stability to meet the needs of different application scenarios.
[0076] Add initiator: Azobisisobutyronitrile (AIBN) is selected as a free radical initiator to initiate the polymerization reaction of the monomer. The amount of initiator added is generally 0.5%-1.5% of the total weight of the monomer. AIBN can decompose at a certain temperature to produce free radicals, thereby initiating the polymerization reaction of the monomer and forming a polymer network.
[0077] The appropriate initiator and its added amount can ensure the smooth progress of the monomer polymerization reaction, forming a polymer network with the expected structure and performance, and providing a guarantee for realizing the microstructural self-repair function of the tape.
[0078] Construction of polymer networks: Solution polymerization to prepare polymers: The synthesized special monomer, crosslinker and initiator are added to the reaction vessel in a set ratio, and then an appropriate amount of organic solvent (such as tetrahydrofuran) is added to form a uniform reaction solution. This solution system is conducive to the uniform mixing of monomers, crosslinkers and initiators, providing a good environment for the smooth progress of the polymerization reaction. After the reaction vessel is sealed, it is placed in a constant temperature water bath with the temperature controlled at 60-70°C and the reaction time is 6-8 hours. Within this temperature range, the initiator can effectively decompose to produce free radicals, initiate monomer polymerization, and avoid excessive temperature causing the destruction of the polymer network structure. During the reaction process, the uniformity of the reaction system is maintained by a stirring device, so that the monomers are fully polymerized to form a polymer network with dynamic chemical bonds.
[0079] The solution polymerization method can precisely control the formation process of the polymer network to obtain a polymer with a uniform structure and good performance, providing high-quality materials for subsequent introduction into the tape microstructure and realizing self-healing function.
[0080] Introducing polymer networks into the tape microstructure: Pretreatment of tape substrate: For the substrate of the double-sided glass fiber mesh fixing tape, such as glass fiber mesh and acrylic adhesive layer, surface activation treatment is first performed. For glass fiber mesh, plasma treatment technology is used, at a power of 100-150W and a treatment time of 3-5 minutes, to produce more active groups on the surface of the glass fiber mesh and enhance the binding force with the polymer network. Plasma treatment can change the chemical composition and physical structure of the glass fiber mesh surface, increase its surface energy, and thus improve the adhesion with the polymer network. For the acrylic adhesive layer, an amine-containing silane coupling agent is used for surface treatment to improve its compatibility with the polymer network. Silane coupling agents can form chemical bonds or strong intermolecular forces between the acrylic adhesive layer and the polymer network, promoting the combination of the two.
[0081] The tape matrix that has undergone surface activation treatment can better combine with the polymer network, ensuring that the polymer network exists stably in the tape microstructure, and can effectively exert its self-repair function to improve the overall performance of the tape.
[0082] Polymer network loading: The prepared polymer solution is loaded onto the pretreated tape substrate by the dipping method. The tape substrate is completely immersed in the polymer solution for 10-15 minutes to allow the polymer to fully penetrate into the microstructure of the tape. Then, the solvent is removed by slowly increasing the temperature (such as from room temperature to 40-50°C) to allow the polymer to solidify and form in the microstructure of the tape, forming a polymer network with self-healing capabilities. The dipping method can evenly distribute the polymer solution in the microstructure of the tape substrate, and slowly increasing the temperature to cure can avoid defects in the polymer network caused by rapid temperature changes.
[0083] Through this method, a polymer network with self-healing ability was successfully introduced into the microstructure of the tape, giving the tape the function of microstructural self-repair. It can automatically repair itself when damaged by external forces, thus extending its service life.
[0084] Design and optimization of tape microstructure: Microstructural stress concentration design: Constructing microscopic defect structures: During the preparation of the tape, microscopic defect structures, such as microcracks or micropores, are introduced into specific areas of the tape through micro-nano processing technologies such as photolithography or template method. The size and distribution of these microscopic defect structures are precisely designed. For example, the length of microcracks is controlled at 1-5 microns, the diameter of micropores is 0.5-2 microns, and they are distributed periodically on the surface of the tape. When the tape is damaged by external forces, these microscopic defect structures can preferentially generate stress concentration, providing trigger signals for the breaking and recombination of dynamic chemical bonds.
[0085] The design of the micro-defect structure enables the tape to more effectively trigger the self-repair mechanism when subjected to external force, thereby improving the timeliness and efficiency of self-repair and ensuring that the tape can maintain good performance under various complex working conditions.
[0086] Adjust material distribution: In the microstructure of the tape, the distribution of different materials is reasonably adjusted. For example, in the area close to the surface, the content of the polymer network is appropriately increased so that it can respond to stress concentration more effectively when damaged and quickly start the self-repair mechanism; inside the tape, the distribution of the glass fiber grid and acrylic adhesive layer is optimized to ensure the overall mechanical properties and stability of the tape.
[0087] The optimized material distribution not only ensures the self-healing performance of the tape, but also takes into account its overall mechanical properties and stability, so that the tape not only has self-healing function, but also can meet the strength and stability requirements of different application scenarios.
[0088] Assisted design to promote dynamic chemical bond breaking and recombination: Introducing stress-sensitive additives: Inorganic nanoparticles with special crystal transformations, such as zirconium oxide nanoparticles, are added to the polymer network as stress-sensitive additives. When the tape is subjected to stress concentration, the crystal form of these nanoparticles will change, resulting in local energy release, further promoting the breaking and recombination of dynamic chemical bonds in the polymer network, and accelerating the self-healing process.
[0089] The addition of stress-sensitive additives significantly improves the speed and effect of self-repair, allowing the tape to restore the damaged microstructure in a shorter time, thereby improving the reliability and practicality of the tape.
[0090] Designing molecular guiding structures: Building structures with molecular guiding functions in polymer networks, such as making polymer molecular chains tend to be arranged preferentially in a specific direction through specific molecular design. When dynamic chemical bonds are broken, molecular fragments can be rearranged and combined more orderly along these guiding structures, improving the accuracy and efficiency of repair.
[0091] The design of the molecular guide structure helps to improve the accuracy and efficiency of the repair, so that the tape can better restore its original performance after repair, ensuring the effectiveness of the tape.
[0092] Performance testing and optimization: Self-healing performance test: Simulated damage experiment: Use micromechanical testing equipment to conduct simulated damage experiments on the prepared tape. For example, use a nanoindenter to apply 5-10mN pressure on the tape surface to produce microscopic indentation damage; or use laser micromachining equipment to create microcrack damage on the tape surface. These simulated damage experiments can truly simulate the damage that the tape may suffer during actual use.
[0093] Evaluation of repair effect: Scanning electron microscopy (SEM) and atomic force microscopy (AFM) are used to observe the microstructural changes of the damaged part before and after repair to evaluate the integrity and accuracy of the repair. At the same time, mechanical properties testing equipment (such as universal material testing machine) is used to test the mechanical properties of the tape before and after repair, such as tensile strength, shear strength, etc., to quantify the degree of self-repair on the performance recovery of the tape.
[0094] Through scientific performance testing methods, the self-healing performance of the tape can be accurately evaluated, providing reliable data support for subsequent performance optimization.
[0095] Performance optimization: Adjust parameters based on test results: According to the results of the self-healing performance test, the composition of the polymer network, microstructure design, and the types and contents of additives are optimized and adjusted. For example, if the self-healing speed is found to be slow, the content of stress-sensitive additives can be appropriately increased, or the design of the molecular guide structure can be adjusted; if the mechanical properties after repair are not restored to their ideal state, the cross-linking density and material distribution of the polymer network can be re-optimized.
[0096] Multiple rounds of experimental iterations: After many parameter adjustments and experimental tests, the microstructural self-healing performance of the tape is continuously optimized until the expected performance indicators are achieved, such as a self-healing efficiency of more than 90%, and the mechanical properties after repair are restored to more than 85% of the original performance.
[0097] Through the performance optimization process, the self-healing performance of the tape is continuously improved so that it can better meet the needs of practical applications and lay a solid foundation for the promotion and application of the product.
[0098] In summary: Improvement of the effect of the first embodiment: Enhanced performance stability: The microstructure self-repair function of Example 2 can promptly repair microscopic damage caused by external forces and other factors during the use of the tape, effectively maintaining the high flame retardancy, high viscosity, high strength and other properties of the tape. For example, in the manufacture of electronic equipment, even if the tape is subjected to frequent micro-vibrations and frictions, the damage to its microstructure can be promptly repaired, ensuring that good viscosity is always maintained, stabilizing electronic components, while continuously maintaining flame retardancy and preventing fire hazards.
[0099] Extended service life: Through the self-repair mechanism, the tape can continuously restore the damaged microstructure, greatly slowing down the rate of performance degradation, thereby significantly extending the service life. In the field of building fire protection, the tape is exposed to the natural environment for a long time, facing temperature changes, humidity changes, and possible mechanical collisions. The self-repair function can keep the tape structurally intact and stable for a long time, reducing the frequency and cost of replacing the tape.
[0100] Its unique advantages: Adapt to extremely complex working conditions: In some extremely complex application scenarios, such as the aerospace field, the tape may be subjected to the combined effects of strong mechanical stress, high and low temperature cycles, radiation, etc. The tape of Example 2 can maintain good performance under these extreme conditions by virtue of its self-healing function, ensuring the normal operation and safety of related components.
[0101] Reduce maintenance costs and risks: Since the tape has the ability to self-repair, it can reduce the frequency and workload of manual maintenance in many applications. For example, in automobile manufacturing, the tape used in the interior and engine compartment of the car can repair itself even if there are some microscopic damages, without the need for frequent inspection and replacement, which reduces the maintenance cost during the use of the car and the potential risks caused by tape failure.
[0102] This self-repairing tape based on the dynamic chemical bond reorganization mechanism of biomimetic can form a differentiated competitive advantage in the market. It has opened up a new direction for the development of the tape industry, attracted more customers who have demand for high-performance and long-life tapes, and expanded the application field and market space of the product.
Claims
1. A highly flame-retardant and high-viscosity glass fiber mesh double-sided fixing tape, characterized in that: include: A first acrylic adhesive (1), a first glass fiber mesh (2), super heat-resistant heat-insulating fiber cotton (3), a second glass fiber mesh (4), a second acrylic adhesive (5), and a release paper (6); The first glass fiber mesh (2) and the second glass fiber mesh (4) are uniformly doped with nano-scale titanium dioxide and silicon dioxide composite additives, and a layer of nano-scale polymer fiber membrane is uniformly covered on the surface of the glass fiber; the surface of the glass fiber presents a microscopic rough structure; the internal fibers present a bionic honeycomb structure and are closely arranged in hexagons; The super heat-resistant heat-insulating fiber cotton (3) uses a new type of ceramic-based composite fiber as the main raw material, and nano-scale aerogel particles are evenly dispersed in the fiber; rare earth compounds with infrared blocking function are also added; the fiber forms a three-dimensional porous network structure in the microstructure, and a nano protective film is provided on the fiber surface; The first glass fiber mesh (2) and the second glass fiber mesh (4) are respectively located on the top and bottom of the super-heat-resistant heat-insulating fiber cotton (3) to form a stable support frame; the first acrylic glue (1) and the second acrylic glue (5) are respectively located on the top and bottom of the first glass fiber mesh (2) and the second glass fiber mesh (4); the release paper (6) is located at the bottom of the second acrylic glue (5) to protect the glue surface.
2. A highly flame-retardant and high-viscosity glass fiber mesh double-sided fixing tape as claimed in claim 1, characterized in that: The glass fiber mesh gluing process includes raw material inspection, primer application, glue layer coating, glue surface inspection, and winding.
3. A highly flame-retardant and high-viscosity glass fiber mesh double-sided fixing tape as claimed in claim 2, characterized in that: The preparation process of super heat-resistant and heat-insulating fiber cotton includes raw material inspection, needling, combing, shaping, testing and winding.
4. A highly flame-retardant and high-viscosity glass fiber mesh double-sided fixing tape as claimed in claim 3, characterized in that: The overall production process includes unwinding, laminating, adhesive surface inspection, winding, slitting, finished product inspection, packaging, labeling, warehousing and shipping.
5. A highly flame-retardant and highly viscous glass fiber mesh double-sided fixing tape as claimed in claim 4, characterized in that: A dynamic chemical bond recombination mechanism based on biomimetics is introduced for microstructure self-repair. A polymer network with reversible chemical bonds is constructed through the synthesis of special monomers and introduced into the tape microstructure.
6. A highly flame-retardant and high-viscosity glass fiber mesh double-sided fixing tape as claimed in claim 5, characterized in that: The synthesis of special monomers is based on the study of dynamic chemical bonds and supramolecular interactions. Monomers containing borate groups or disulfide bonds that can form dynamic covalent bonds and groups with supramolecular interaction capabilities are synthesized, including but not limited to ureidopyrimidone.
7. A highly flame-retardant and highly viscous glass fiber mesh double-sided fixing tape as claimed in claim 6, characterized in that: During the polymer network construction process, a cross-linking agent such as pentaerythritol triacrylate is introduced to adjust the cross-linking density, and an initiator is added, including but not limited to azobisisobutyronitrile to initiate the monomer polymerization reaction.
8. The highly flame-retardant and highly viscous glass fiber mesh double-sided fixing tape according to claim 7, characterized in that: Constructing micro-defect structures and adjusting material distribution are used to concentrate stress in the microstructure, introducing stress-sensitive additives, and designing molecular-guided structures to promote dynamic chemical bond breaking and recombination.
Citation Information
Patent Citations
Atomic oxygen protective coating with physical damage spontaneous repairing function and preparation method thereof
CN108329502A
Stress sensor with self-repairing ability and preparation method thereof
CN109974905A
Fireproof garment based on silica aerogel composite material and preparation method
CN110558646A
Production process of flame-retardant adhesive tape
CN112048256A
Environment-friendly flame-retardant aluminum foil adhesive tape and manufacturing method thereof
CN113845855A
Cited By
Performance control method, system and device for flame-retardant fiber fabric
CN120544756A
A flame retardant fiber fabric performance control method, system and device
CN120544756B